Constitutive Tor2 Activity Promotes Retention of the Amino Acid Transporter Agp3 at Trans-Golgi/Endosomes in Fission Yeast. - Qingbin Liu; Yan Ma; Xin Zhou; Tomoyuki Furuyashiki (PLoS ONE)
Amino acid transporters are located at specific subcellular compartments, and their localizations are regulated by the extracellular availability of amino acids. In yeast, target of rapamycin (TOR) activation induces the internalization of amino acid transporters located at the plasma membrane. However, whether and how TOR signaling regulates other amino acid transporters located at intracellular compartments remains unknown. Here, we demonstrate that in the fission yeast, the TOR inhibitor Torin-1 induces the transfer of several yellow fluorescent protein (YFP)-fused intracellular amino acid transporters, including Agp3, Isp5, Aat1, and Put4, from trans-Golgi/endosomes into the vacuoles. By contrast, the localizations of YFP-fused Can1, Fnx1, and Fnx2 transporter proteins were unaffected upon Torin-1 treatment. There are two TOR isoforms in fission yeast, Tor1 and Tor2. Whereas tor1 deletion did not affect the Torin-1-induced transfer of Agp3-YFP, Tor2 inhibition using a temperature-sensitive mutant induced the transfer of Agp3-YFP to the vacuolar lumen, similar to the effects of Torin-1 treatment. Tor2 inhibition also induced the transfer of the YFP-fused Isp5, Aat1, and Put4 transporter proteins to the vacuoles, although only partial transfer of the latter two transporters was observed. Under nitrogen depletion accompanied by reduced Tor2 activity, Agp3-YFP was transferred from the trans-Golgi/endosomes to the plasma membrane and then to the vacuoles, where it was degraded by the vacuolar proteases Isp6 and Psp3. Mutants with constitutively active Tor2 showed delayed transfer of Agp3-YFP to the plasma membrane upon nitrogen depletion. Cells lacking Tsc2, a negative regulator of Tor2, also showed a delay in this process in a Tor2-dependent manner. Taken together, these findings suggest that constitutive Tor2 activity is critical for the retention of amino acid transporters at trans-Golgi/endosomes. Moreover, nitrogen depletion suppresses Tor2 activity through Tsc2, thereby promoting the surface expression of these transporters.